1996
DOI: 10.3109/00048679609062656
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Patient's Right to Confidentiality and the Family's Need to Know

Abstract: Rather than assuming that confidentiality is an intransient problem, the authors conclude that dealing with the question of confidentiality sensitively presents clinicians with an opportunity to develop quality relationships with both clients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Concerns about confidentiality are sometimes used as a reason to avoid SPs, and staff may have fears of disrupting the relationship formed with their participant or breaking the law (Gray et al, 2008;Furlong & Leggatt, 1996;Nicholis & Pernice, 2009;Wynaden & Orb, 2005). Providers often lack experience dealing with these conflicts as well as not having the experience or the education to know how to work with and collaborate with SPs (Kaas et al, 2003;Kim & Salyers, 2008).…”
Section: Barriers To Including Families and Sps In Carementioning
confidence: 96%
“…Concerns about confidentiality are sometimes used as a reason to avoid SPs, and staff may have fears of disrupting the relationship formed with their participant or breaking the law (Gray et al, 2008;Furlong & Leggatt, 1996;Nicholis & Pernice, 2009;Wynaden & Orb, 2005). Providers often lack experience dealing with these conflicts as well as not having the experience or the education to know how to work with and collaborate with SPs (Kaas et al, 2003;Kim & Salyers, 2008).…”
Section: Barriers To Including Families and Sps In Carementioning
confidence: 96%
“…Formalising the rights of families/whanau in the compulsory assessment and treatment process was also informed by a growing recognition of the importance of family collaboration and involvement in die care, treatment, and recovery of people who experience mental health illnesses (Petrila & Sadoff (1992), Furlong & Leggat (1996), Szmukler & Bloch (1997, Emmet (1998)). …”
Section: New Zealand Government's Drive To Formalise the Rights Of Famentioning
confidence: 99%
“….Professionals deny themselves access to the wisdom of carers and hinder early diagnosis and accurate diagnosis. (MHCA, 2005; ARAFMI Tasmania, Submission #245) These problems exist despite the spirit of the various state and Commonwealth mental health policies that proclaim partnership between family carers and service providers, and various reports in the research literature about the management of confidentiality matters with family (Furlong & Leggatt, 1996;Veccio, Stephens, and Cybinski [2007]) studied Australian carer perceptions of service delivery and found that most carers reported that they received insufficient support from service providers. A recent survey of family carers by the Mental Health Council of Australia (MHCA, 2009) also confirmed that carers continue to feel ignored and excluded by treatment services.…”
Section: The Need For a Commitment To The Principles Of Inclusion Andmentioning
confidence: 99%
“…Between these extremes is a range of care situations in which the needs and rights of the patient compete with the needs and rights of the family. The seminal work of Furlong and Leggatt (1996) remains relevant to managing this tension. They suggested that dealing with the question of confidentiality sensitively presents clinicians with an opportunity to develop quality relationships with both clients and their families (Furlong & Leggatt, 1996).…”
Section: The Need For a Commitment To The Principles Of Inclusion Andmentioning
confidence: 99%